Determination of the total acid number of Brazilian crude oil samples: Theoretical and experimental evaluation of three standard methods. (1st April 2022) - Decote, Paulo A.P.; Negris, Luana; Vidoto, Amanda P.; Mendes, Luiz A.N.; Flores, Erico M.M.; Vicente, Maristela A.; Santos, Maria F.P.
Graphical abstract: Highlights: Three standard methods of total acid number (TAN) determination were compared. Method scope, working range, precision, and effects of interferences were assessed. The methods were used to determine the TANs of four Brazilian crude oil samples. Sample solubility/size & hydrolyzable salt type/content affected method precision. Abstract: The total acid number (TAN) is commonly used to assess the quality of crude oil, petroleum products, lubricants, biodiesel, and biodiesel blends and can be determined using several standard methods. The validation of these methods usually involves the estimation of their precision, which is related to repeatability and reproducibility. Herein, we theoretically compare the performances of potentiometric (ASTM D664 and ABNT NBR 14448) and thermometric (ASTM D8045) standard methods of TAN determination in terms of sample type scope, operational TAN range, precision, and the effects of interferents. In addition, these methods are used to experimentally determine the TANs of four Brazilian crude oil samples (API gravity = 13.2–31.0), and the precision of these values is found to be affected by sample solubility, sample size, and hydrolysable salt type and content. Thus, our work provides valuable reference information and facilitates the selection of optimal TAN determination methods, which should ultimately help minimize the adverse environmental and financial effects of inaccurate TAN determination in the oil refining and production chain.